Gambaran Aktivitas Fungsional Penderita Osteoarthritis Lutut Yang Menggunakan Knee Support - Yulia Agitatik Mentari (Jurnal Keterapian Fisik, 2018)
Abstract : Osteoarthritis, Functional Activity, Knee Support. Knee osteoarthritis is a chronic inflammation of the knee joint characterized by a decrease in muscle value and an impact on decreased knee joint stability resulting in decreased ability of a person to perform functional activities. The ability of functional activity is directly related to quality of life and its assessment is very important in clinical practice. The decrease in functional activity of knee osteoarthritis patient can be minimized by the use of knee support. The purpose of this study was to determine the effect of knee support on functional activity in patient with knee osteoarthritis. This study used qualitative research method with one subject of knee osteoarthritis. The result of this research there are some progress of the subject when performing functional activity that she could not do. The conclusion obtained is the use of knee support within six weeks can increase the functional activity of patients with knee osteoarthritis degree three. As for suggestions that can be given for researchers who want to continue this research is to add research subjects and also pay attention to uncontrolled factors cause knee osteoarthritis.